Effect of Egg White Combined with Chalcanthite on Lipopolysaccharide induced Inflammatory Cytokine Expression in RAW 264.7 cells - Choi Eun-A; Yoon Jeung-Won; Choi Hak-Joo; Kim Dong-Hee; Yoo Hwa-Seung (Korean Pharmacopuncture Institute, 2012)
Historically, mineral compound herbal medicines have long been used in treatments of immune-related diseases in Korea, China and other Asian countries. In this study, we inv-estigated the anti-inflammatory effect of egg white combined with chalcanthite (IS4) on lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. RAW 264.7 cells cultured with LPS and various con-centrations of IS4 were analyzed to determine the production of pro-inflammatory cytokines and mediators by using enzyme-linked immune sorbent assays (ELISAs). IS4 concentration inhibited the production of interleukin-1beta (IL-1β), interleukin-6 (IL-6), and granulocyte-macrophage colony-stimulating factor (GM-CSF) induced by LPS. IS4 at high concentrations (25 and 50`㎍/ml) inhibited, in concentration-dependent manner, the expression of tumor necrosis factor-alpha (TNF-α) stimulated by LPS. IS4 has shown an anti-inflammatory effect in RAW 264.7 cells.